2012
DOI: 10.1155/2012/508902
|View full text |Cite
|
Sign up to set email alerts
|

Epicatechin Used in the Treatment of Intestinal Inflammatory Disease: An Analysis by Experimental Models

Abstract: Background. This study was pathway of (−)-epicatechin (EC) in the prevention and treatment of intestine inflammation in acute and chronic rat models. Methods. Intestine inflammation was induced in rats using TNBS. The morphological, inflammatory, immunohistochemical, and immunoblotting characteristics of colon samples were examined. The effects of EC were evaluated in an acute model at doses of 5, 10, 25, and 50 mg/kg by gavage for 5 days. The chronic colitis model was induced 1st day, and treated for 21 days.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…Another study found that (−)-epicatechin treatment improved acute intestinal inflammatory disease. At a concentration of 10 mg/kg in rats induced with trinitrobenzenesulfonic acid, there was a reduction in colitis including less ulceration and disorganization of the tissue after histological analysis [ 48 ]. In addition, the authors observed significantly higher levels of glutathione in the colon tissue of animals treated with (−)-epicatechin.…”
Section: Beneficial Health Effects Of Selected Flavonoid Compoundsmentioning
confidence: 99%
“…Another study found that (−)-epicatechin treatment improved acute intestinal inflammatory disease. At a concentration of 10 mg/kg in rats induced with trinitrobenzenesulfonic acid, there was a reduction in colitis including less ulceration and disorganization of the tissue after histological analysis [ 48 ]. In addition, the authors observed significantly higher levels of glutathione in the colon tissue of animals treated with (−)-epicatechin.…”
Section: Beneficial Health Effects Of Selected Flavonoid Compoundsmentioning
confidence: 99%
“…In this context, natural products have been used for many years as a source for the discovery of these molecules. As previously reported, (−)-epicatechin (a main component of the cacao and a derivative product of cocoa) is a molecule that shows several beneficial health effects such as anti-inflammatory [15], antibacterial [22], cardio protector [23], and cognitive health benefits [24]. However, there are few studies focusing on its anticancer activity and the associated mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…However, its poor stability, absorption, and hepatotoxicity have limited its use [12]. Another flavonoid with important biological activity is (−)-epicatechin ( Figure 1), which is a molecule that has been described to have antioxidant [13,14], anti-inflammatory [15], cardiovascular [16] and anticancer [17][18][19] properties. [20], and, in comparison to (−)-epigallocatechin-3-gallate (EGCG), it has not shown any side effects.…”
Section: Introductionmentioning
confidence: 99%
“…The rats of this group were administered Dox as group 2 plus epicatechin (dissolved in CMC 1% solution) by oral gavage at a dose of 25 mg/5 ml/kg b.w. every other day for 6 weeks 18 .…”
Section: Group 4 (Dox-administrated Rats Treated With Epicatechin)mentioning
confidence: 99%